La violencia en escena: Cuerpo, narcotráfico y espacio público en el México contemporáneo - Nuria Carton de Grammont (Les Cahiers ALHIM)
In the context of war against drug trafficking that Mexico is now facing, the concept of corpse has taken on particular importance as a social actor and as the expression of media materials that initiates an exposure device in the public space to mobilize different audiences, social stakeholders and power relationships. The images filtered by the medias show more than only simple remains left behind at the crime scene. The public space becomes the stage where all these installations show off the terror which marks the domination of the territory over the enemy. Far from morbidity and horror, this compels us to ask questions about the geopolitical relations between the State and organised crime, as well as on the visibility and the objectives of such extreme images